A Lifespan Developmental-Stage Approach to Tobacco and Other Drug Abuse Prevention. (18th April 2013) - Sussman, Steve
Abstract : At least by informal design, tobacco and other drug abuse prevention programs are tailored to human developmental stage. However, few papers have been written to examine how programming has been formulated as a function of developmental stage throughout the lifespan. In this paper, I briefly define lifespan development, how it pertains to etiology of tobacco and other drug use, and how prevention programming might be constructed by five developmental stages: (a) young child, (b) older child, (c) young teen, (d) older teen, and (e) adult (emerging, young-to-middle and older adult substages). A search of the literature on tobacco and other drug abuse prevention by developmental stage was conducted, and multiple examples of programs are provided for each stage. A total of 34 programs are described as examples of each stage (five-young children, 12-older children, eight-young teens, four-older teens, and five-adults). Implications for future program development research are stated. In particular, I suggest that programming continue to be developed for all stages in the lifespan, as opposed to focusing on a single stage and that developmentally appropriate features continues to be pursued to maximize program impact.